2015
DOI: 10.1155/2015/531756
|View full text |Cite
|
Sign up to set email alerts
|

Research on Charging Combination Based on Batch Weight Fit Rule for Energy Saving in Forging

Abstract: As a traditional high energy-consuming industry, the forging industry consumes a lot of energy. The activity consuming the highest energy during forging process is the heating. The problem regarding how to separate workpieces with the same holding temperature and holding time and combine them for charging in forging was analyzed and a model based on batch weight fit rule for optimizing the charging combination with the goal of energy saving was proposed. A genetic algorithm was adopted to optimize and solve th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
2
0
3
Order By: Relevance
“…Paper [1] analyzed different forging techniques for forgings of special purpose. It was found that these forging techniques differ in the type of the applied forge operations, thermomechanical deformation modes, and the use of specialized forge tools [2].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Paper [1] analyzed different forging techniques for forgings of special purpose. It was found that these forging techniques differ in the type of the applied forge operations, thermomechanical deformation modes, and the use of specialized forge tools [2].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The upsetting operation for cylindrical billets does not contribute to the closure of axial defects in forge ingots. It is a relevant field of research to improve the upsetting operation through the preliminary profiling of a cylindrical workpiece [1], which would make it possible to alter the stressed-strained state of a billet's metal and would contribute to welding internal defects.…”
Section: Introductionmentioning
confidence: 99%
“…В результаті збільшується час механічної обробки, підвищуються витрати металу і відбувається перерізання волокна. Це пов'язано з тим, що при довжині пустотілих заготовок більш 400 мм та діаметрі отвору менше 30 мм використання оправки під час протягування неможливо [5]. Тому проблема виготовлення заготовок товстостінних пустотілих заготовок на сьогодні є актуальною, яка потребує всебічного аналізу та удосконалення [6].…”
unclassified
“…У дослідженнях [6] представлений метод осадження з обертанням верхнього інструменту, що деформує. Цей метод сприяє зменшенню викривлення форми заготовки після осадження.…”
unclassified